Accuracy of point-of-care ultrasound by pediatric emergency physicians for testicular torsion. Issue 6 (December 2019) - Friedman, N.; Pancer, Z.; Savic, R.; Tseng, F.; Lee, M.S.; Mclean, L.; Bagli, D.J.; Tessaro, M.O.
Summary: Introduction: Acute scrotum is a common presentation to the pediatric emergency department, and ultrasound is frequently used to narrow the differential diagnosis. Point-of-care ultrasound (POCUS) is increasingly used by urologists and emergency physicians and could potentially be used to detect pediatric testicular torsion. Objectives: This study aimed to determine the accuracy of POCUS by pediatric emergency physicians in diagnosing testicular torsion and the agreement between point-of-care ultrasound and final diagnosis for other causes of acute scrotum. Study design: A chart review of patients presenting to the study emergency department who received POCUS by a pediatric emergency physician, as well as radiology department ultrasound and/or surgery, was performed. Charts were reviewed for POCUS diagnoses, final diagnoses, and imaging time metrics. Results: A total of 120 patients met study criteria, with 12 cases of testicular torsion. The diagnostic accuracy of POCUS for testicular torsion is described in the summary table. For all causes of acute scrotum, point-of-care ultrasound agreed with final diagnosis in 70% (95% confidence interval [CI] 62–78%) of cases, and more experienced point-of-care ultrasound users displayed higher agreement with final diagnosis. Point-of-care ultrasound results were generated a median of 73 min (Q1 = 51, Q3 = 112) before radiology department ultrasound results. Discussion: Scrotal POCUS performed by pediatric emergency physicians appears to be an accurate tool to detect testicular torsion in children with acute scrotum and saves time compared with radiology ultrasound. The study results may not be generalizable to hospitals without a multidisciplinary POCUS system for quality assurance and image sharing. Future work on POCUS for acute scrotum should investigate its impact on patient outcomes, cost-effectiveness, and family satisfaction. Conclusion: Point-of-care ultrasound by pediatric emergency physicians is accurate for detecting testicular torsion in children with acute scrotum and could expedite diagnosis of this time-sensitive condition. Table Accuracy of POCUS by pediatric emergency physicians in diagnosing testicular torsion in children with acute scrotum. Table Sensitivity (%, 95% CI) 100 (73.5–100) Specificity (%, 95% CI) 99.1 (95.0–100) PPV (%, 95% CI) 92.3 (63.0–98.8) NPV (%, 95% CI) 100 (NC a ) +LR (95% CI) 108.0 (15.4–759.8) −LR (95% CI) 0 (NC a ) CI, confidence interval; PPV, positive predictive value; NPV, negative predictive value; POCUS, point-of-care ultrasound; LR, likelihood ratio. a NC = non-calculable.